Hubungan Pengetahuan, Sikap, Dan Dukungan Suami Dengan Pemilihan KB IUD Pasca Persalinan DI RSUD Budhi Asih Jakarta Tahun 2022: The Relationship Between Knowledge, Attitudes and Husband's Support with Selection of Postpartum IUD Contraception in Budhi Asih Jakarta Hospital in 2022 - Rhofitriastiti, Dyah Niken (Indonesian Scholar Journal of Nursing and Midwifery Science, 2023)
Introduction: Postpartum family planning services are still low, even though they have high effectiveness. This can be seen in the City of East Jakarta, only 6.81%. Budhi Asih Hospital, Jakarta, in 2021 from 820 births, post-delivery IUD users were found to be 564 people with an average of 31 to 32 people per month. There are several factors that do not support the use of the IUD contraceptive method including the mother's knowledge, attitude, and husband's support. The purpose of the study was to determine the relationship between knowledge, attitude, and husband's support with the use of the IUD Postpartum KB at Budhi Asih Hospital, Jakarta in 2022. Methods: Quantitative analytic research method with a cross-sectional design, the number of samples was 52 respondents, the sampling technique was accidental sampling, and the data analysis used the test chi-square. Results: The results of the study mostly did not choose the IUD after childbirth 61,5%; with low knowledge 67,3%; negative attitude 53,8%; and a supporting husband 48,1%. The results of the bivariate analysis showed that there was a relationship between knowledge (p-value = 0,000), attitude (p-value = 0,000), and husband's support (p-value = 0,019) with the choice of postnatal IUD KB. Discussion: The conclusion of the research is that there is a relationship between knowledge, attitude, and husband's support with the selection of post-delivery IUD family planning. It is hoped that pregnant women will be more diligent in consulting health facilities and seek more health information through the media, the internet, and health workers about the goals and benefits of post-delivery IUD contraception so that mothers are more motivated to use the IUD after delivery.